1983
DOI: 10.1017/s0022172400060009
|View full text |Cite
|
Sign up to set email alerts
|

The excretion of Salmonella typhimurium in the faeces of calves fed milk substitute

Abstract: SUMMARYA total of 495 calves in 16 batches were examined (117 calves in 4 batches in 1979 and 378 in 12 batches in 1982). They were purchased in markets, transported by road to a farm in Somerset and reared on a milk substitute diet for a period of up to five weeks. Salmonella typhimurium phage type DT 193 was endemic in 1979 and phage type DT 204c in 1982. The mortality rates in the two years were 9S4 % and 1-9% respectively. The causes of death were not investigated although the majority were probably due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
0
11
1
Order By: Relevance
“…Indeed on one of the premises (Fig. 1) the salmonella isolation rates increased after cleaning and disinfection and it has been suggested that the use of pressure hoses may cause aerosols and spread salmonellas to other parts of the building [11]. It is also possible that vigorous cleansing and disinfection may have washed salmonellas out from previously untouched areas.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed on one of the premises (Fig. 1) the salmonella isolation rates increased after cleaning and disinfection and it has been suggested that the use of pressure hoses may cause aerosols and spread salmonellas to other parts of the building [11]. It is also possible that vigorous cleansing and disinfection may have washed salmonellas out from previously untouched areas.…”
Section: Resultsmentioning
confidence: 99%
“…It is probable that these animals contracted infection either on their farm of origin, or in the market or markets through which they passed, or from the lorry or lorries in which they were transported. S. newport, a serotype which had not been isolated by us previously in this farm (Linton, Timoney & Hinton, 1981;Hinton & Linton, 1982;Hinton et al 1983 and unpublished observations) was probably contracted from one of these sources since in three of the four exeretors it was first isolated within three days of their arrival on the farm.…”
Section: Discussionmentioning
confidence: 67%
“…This investigation represents an extension of studies carried on this farm in 1979 and 1982 (Hinton et al 1983). In the event the situation in shed A was not strictly comparable with the earlier years since the incidence of salmonella infection was lower, and in one batch, a serotype other than S. typhimurium, namely S. newport, was isolated.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations